Pengaruh Influencer Marketing dan Kualitas Pelayanan Terhadap Minat Beli Pelanggan dengan Keputusan Pembelian sebagai Variabel Intervening pada Skincare Ms Glow Padang - Bricilla Telaumbanua; Marta Widian Sari; Della Asmara Putri (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This study aims to find out how much influence influencer marketing and service quality on customer buying interest with purchase decisions as an intervening variable in Ms Glow Padang skincare. The Data Analysis Method is in the form of Questionnaire Data with a Sample of 91 respondents. The data analysis method used is the analysis of questionnaire data types. The results of the study obtained based on a partial test (T test) were obtained: There is a significant influence of influencer marketing on purchase decisions. There is a significant influence of service quality on purchasing decisions. There is a significant influence of influencer marketing on buying interest. There is an insignificant influence of service quality on buying interest. There is a significant influence of purchasing decisions on buying interest. There is a significant influence of influencer marketing on buying interest through purchasing decisions. There is a significant influence of service quality on buying interest through purchase decisions.